2009
DOI: 10.1590/s0004-282x2009000600010
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise in rats with epilepsy is protective against seizures: evidence of animal studies

Abstract: -People with epilepsy have been discouraged from participating in physical activity due to the fear that it will exacerbate seizures. Clinical and animal studies indicate a reduction of seizure frequency as well as decrease susceptibility to subsequently evoked seizures after an exercise program. Analyses from experimental studies of animals with epilepsy submitted to physical training programs were performed. In all studies the physical training was able to reduce the number of spontaneous seizures in rats wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…For example, exercise has been found clinically to reduce depressive symptoms in mild to moderately affected patients, and wheel running produces antidepressant-like behaviors in a variety of rodent models of stress and depression compared with sedentary controls [27]. Likewise, exercise has anticonvulsant effects in several rodent seizure models [17, 28, 29], and some clinical benefit has been seen in preliminary human studies [30-32]. Importantly for this proposal, epileptics who are physically active have significantly lower levels of depression than inactive subjects [33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, exercise has been found clinically to reduce depressive symptoms in mild to moderately affected patients, and wheel running produces antidepressant-like behaviors in a variety of rodent models of stress and depression compared with sedentary controls [27]. Likewise, exercise has anticonvulsant effects in several rodent seizure models [17, 28, 29], and some clinical benefit has been seen in preliminary human studies [30-32]. Importantly for this proposal, epileptics who are physically active have significantly lower levels of depression than inactive subjects [33].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time as restriction and overprotection are put into action, clinical 3,9,11,12 and experimental studies [13][14][15] have shown positive effects of exercise in epilepsy. For instance, most experiments on brain electrical activity have shown that abnormal discharges disappear in most patients during physical activity but return at rest 11,16 . It has been also observed that fewer seizures occur during both mental and physical activity compared with periods of rest 18,19 .…”
mentioning
confidence: 99%
“…It has been also observed that fewer seizures occur during both mental and physical activity compared with periods of rest 18,19 . The increased vigilance and attention involved in exercise could explain the reduction in the number of seizures 16 . In animal studies, a reduction of seizure frequency was observed after an aerobic physical training 14,19 .…”
mentioning
confidence: 99%
“…Rats with pilocarpineinduced epilepsy submitted to a physical training program presented a lower frequency of spontaneous seizures than controls. 19,20,46,48,49 A very low probability of exercise-induced seizures was found and no sudden death occurred while exercising. Even strength training (climbing series with progressively heavier load) improved seizure frequency.…”
Section: The Influence In Seizure Induction and Controlmentioning
confidence: 93%
“…25 Nevertheless, clinical investigation presents several limitations, such as lack of appropriate controls and the presence of potential confounders, like compliance to physical exercise and to AEDs therapy. 48 Some human researches have been more successful than others. Nakken et al 14 studied twenty-one patients with uncontrolled epilepsy submitted to aerobic physical exercise for four weeks, and no difference between seizure frequency two weeks before, during, or two weeks after the exercise program was found.…”
Section: The Influence In Seizure Induction and Controlmentioning
confidence: 99%